151 Confirmed Safety of Deutet.rabenazine for Tardive Dyskinesia in a 3-Year Open-Label Extension Study. (April 2020) - Fernandez, Hubert H.; Barkay, Hadas; Hauser, Robert A.; Factor, Stewart A.; Jimenez-Shahed, Joohi; Gross, Nicholas; Marinelli, Leslie; Gordon, Mark Forrest; Savola, Juha-Matti; Anderson, Karen E.
Abstract: Background: Deutetrabenazine (Austedo) is approved by the FDA for treatment of tardive dyskinesia (TD) in adults. In the 12-week ARM-TD and AIM-TD studies, deutetrabenazine showed clinically significant improvements in Abnormal Involuntary Movement Scale (AIMS) scores compared with placebo, and there were low rates of overall adverse events (AEs) and discontinuations associated with deutetrabenazine. The objective of this study was to evaluate the long-term safety and tolerability of deutetrabenazine in patients with TD at 3 years. METHODS: Patients who completed ARM-TD or AIM-TD were included in this open-label, single-arm extension study, in which all patients restarted/started deutetrabenazine 12 mg/day, titrating up to a maximum total daily dose of 48 mg/day based on dyskinesia control and tolerability. The study comprised a 6-week titration period and a long-term maintenance phase. Safety measures included incidence of AEs, serious AEs (SAEs), and AEs leading to withdrawal, dose reduction, or dose suspension. Exposure-adjusted incidence rates (EAIRs; incidence/patient-years) were used for calculating AE frequencies. This analysis reports results up to Week 158. RESULTS: A total of 343 patients were enrolled (111 received placebo and 232 received deutetrabenazine in the parent studies). At the time of this analysis, 183 patients were still receiving treatment; 259 completed 1 year, 172 completed 2 years, and 41 completed 3 years. There were 623 patient-years of exposure. More than 40% of patients reached the maximum dose. EAIRs of AEs were comparable to or lower than those observed in the ARM-TD and AIM-TD short-term randomized trials of deutetrabenazine vs. placebo. The frequency of SAEs (EAIR 0.10) was similar to that observed with short-term placebo (0.33) and short-term deutetrabenazine (range 0.06–0.33) treatment. AEs leading to withdrawal (0.06), dose reduction (0.10), and dose suspension (0.05) were uncommon. CONCLUSION: These results support the safety outcomes observed in the ARM-TD and AIM-TD parent studies and the safety of deutetrabenazine for long-term use in patients with TD. Funding Acknowledgements: This study was funded by Teva Pharmaceuticals, Petach Tikva, Israel